New data and threat status of two rare North African species of the subgenus Bolognaia (Coleoptera: Meloidae: Meloini: Eurymeloe) - Alberto Sánchez Vialas; José Luis Ruiz; Alain Roujas; Alexandre François (Graellsia)
This study updates the distribution and conservation status of two poorly documented blister beetle species in Morocco: Eurymeloe (Bolognaia) pallidicolor (Martínez de la Escalera, 1909) and E. (B.) saharensis (Chobaut, 1898). A new locality for E. pallidicolor is added, which represents the southernmost known occurrence for the species, along with a total of seven new localities for E. saharensis in both the southwest and southeast of Morocco, significantly expanding its known area of occupancy in the country. A preliminary assessment of the threat status for both species is conducted based on IUCN criteria. Additionally, the habitat characteristics of both species in Morocco are described. While E. saharensis faces no immediate threats, E. pallidicolor appears to be a stenotopic species confined to low-altitude coastal and subcoastal areas. Its extent of occurrence and area of occupancy are very limited, which would place E. pallidicolor in an unfavorable conservation status. However, due to the limited available information, it would qualify as “Data Deficient” species according to the IUCN criteria. These findings emphasize the crucial role of natural protected areas, such as Souss-Massa National Park, in supporting populations of species affected by habitat destruction in the region. Lastly, a brief comment on the internal taxonomy of the genus Eurymeloe is provided, and a new combination is established: Eurymeloe (Bolognaia) digiuliorum (Bologna, Riccieri & Spagoni, 2024) comb. nov.